Pengembangan Keterampilan Berpikir Positif melalui Layanan Konseling Kelompok bagi Anggota Ikatan Mahasiswa Pemuda Pelajar Semurup, Kota Padang - Hengki Yandri; Alfaiz Alfaiz; Dosi Juliawati (Jurnal Pengabdian Pada Masyarakat, 2019)
DEVELOPING A POSITIVE THINKING SKILL OF IMPPS MEMBERS THROUGH GROUP COUNSELING SERVICE. Activities of community service was based on a phenomena about lack of student’s positive thinking skill and there are not functional optimally in a positive way. The purpose of this service is to developing a positive thinking skill of IMPPS members in Padang through group counseling service. The implementation method used consist of five phase which is 1) Shaping, 2) Transition, 3) Intervention, 4) Conclusion, and 5) Closing service. A total participant was 50 students of IMPPS Member. Result of this service was a member of IMPPS Padang has a knowledge, paradigm, and positive thinking skill in their activities in social and learning.